PELAKSANAAN RENCANA INDUK PEMBANGUNAN KEPARIWISATAAN DAERAH KABUPATEN KAMPAR TAHUN 2010-2015 - Pratama, Vito; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
With magnitude potential owned tourism by Kampar, then Local Government District. Kampar do an important step by organizing tourism potentials owned by Kampar Regency. The main steps that should be carried out within the framework of the development of the tourism sector Kampar District is preparing a Plan Regional Tourism Development Master Kampar, then expected able for improve development tourism in Kampar. By because that aim research this is for knowing implementation Plan Regional Tourism Development Master Kampar.The method used in writing research this is approach qualitatively. Informants of this study were chosen purposively based on characteristics or specific characteristics based on research needs. That is 7 people.As for results research RIPKD implementation Kab. Kampar are: 1) lack of work same government with developers tourism, 2) has not existence promotion done government constrained because inadequate budget and source power human, 3) formation group conscious tours this not yet accomplished. While obstacles is 1) Situation people are still not yet can for receive climate tourism whole, 2) Presence in part object still travel located in in Forest custom and Forest protection, 3) Presence object Scattered travel make hard for formed ka-bag ntong destination travel.With existence barriers, then efforts that could do are: 1) Increasing Cooperation. 2) Development Investment, 3) Development Infrastructure, 3) Formation Destinations Featured, 4) Increased Promotion to Regional Affairs / Interior., 5) Formation Institutional, 6) Participation Society, 7) Awareness SocietyWord Keywords: Implementation RIPKD